PENGARUH PEMBELAJARAN ORGANISASI, MOTIVASI DAN KEPEMIMPINAN TERHADAP KINERJA TENAGA KEPERAWATAN DI RUMAH SAKIT UMUM DAERAH KABUPATEN SIAK - Putri, Kaida; Harlen, Harlen (Jurnal Tepak Manajemen Bisnis, 2017)
Organization Study, Motivation and Leadership To Performance TreatmentEnergy in Sub-Province Area Public Hospital Siak.Research is done in Rumah SakitUmum Daerah (RSUD) Kabupaten Siak in having address King Kecik road No. 01Kampung Dalam, Siak Sri Indrapura Kabupaten Siak. Research is started from Februari2015 up to August 2016. Sample in this research is 68 or all population. Sampling basedon census method. While to analyse data, writer applies doubled linear regression methodwith help of fighting SPSS Versi 170.Based on test result f it is known that organizationstudy variable (X1), motivation of job (X2) and leadership (X3) joinly influential to treatmentenergy performance in Rumah Sakit Umum Kabupaten Siak. Based on test result tindicates that organization study variable (X1), motivation of job (X2) and leadership (X3)influential directly to treatment energy performance in Rumah Sakit Umum DaerahKabupaten Siak.Based on coefficient of determination test result (R2) obtained R Square0628. This value then will be altered to form of gratuity. This mean contribution percentageof organization study variable influence (X1), motivation of job (X2) and leadership(X3) to treatment energy performance in Rumah Sakit Umum Daerah Kabupaten Siakequal to 62,8% while the rest 37,2% influenced by other variable of which is not checkedin this research.